Computational modeling for the computer animation of legged figures - Girard, Michael, author; Maciejewski, Anthony A., author; ACM, publisher (Colorado State University. Libraries, 1985)
Modeling techniques for animating legged figures are described which are used in the PODA animation system. PODA utilizes pseudoinverse control in order to solve the problems associated with manipulating kinematically redundant limbs. PODA builds on this capability to synthesize a kinematic model of legged locomotion which allows animators to control the complex relationships between the motion of the body of a figure and the coordination of its legs. Finally, PODA provides for the integration of a simple model of legged locomotion dynamics which insures that the accelerations of a figure's body are synchronized with the timing of the forces applied by its legs.
Keywords: motion control; graphics; realism; animation; computational modeling; manipulators; legged locomotion